228k views
2 votes

\frac{x {}^(2) - 4 }{ \sqrt{x {}^(2) - 6x + 9 } } \geqslant 0


User Sam French
by
5.5k points

1 Answer

3 votes

First of all, we can observe that


x^2-6x+9 = (x-3)^2

So the expression becomes


(x^2-4)/(√((x-3)^2)) = (x^2-4)/(|x-3|)

This means that the expression is defined for every
x\\eq 3

Now, since the denominator is always positive (when it exists), the fraction can only be positive if the denominator is also positive: we must ask


x^2-4 \geq 0 \iff x\leq -2 \lor x\geq 2

Since we can't accept 3 as an answer, the actual solution set is


(-\infty,-2] \cup [2,3) \cup (3,\infty)

User Shreyes
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.